PURWARUPA ALAT PENDETEKSI KEBAKARAN JARAK JAUH MENGGUNAKAN PLATFORM THINGER.IO - reisditama ramadhon; Wahyu Kusuma Raharja (Electro Luceat, 2021)
Fires that occur at this time when the house is left empty by the owner Fires cannot be estimated at the place and time, and will occur at any time so that tools are needed to detect fire events. Currently, most of the fire detection tools are still not integrated by the internet and the fire department, which results in delays in the arrival of the fire department to the location.For this reason, a home fire detector was made using the Thinger.Io platform as a server to display the occurrence of fires in a house. This tool uses NodeMCU ESP8266 as a connection to the internet. There are two sensors used, namely a flame sensor and a DHT11 sensor and several electronic components used including relays, water pumps, and buzzers. The test is carried out by sending data using the NodeMCU ESP8266 in real-time to the Thinger.Io platform.Based on tool testing, the tool can work well. The results of the comparison of the DHT11 sensor value with the thermometer produce an error percentage value of 1.4%. The results of testing the delay in the process of sending data from the device to the Thinger.Io platform require an average of 03.04 seconds later for testing the accuracy of GPS showing accurate coordinates on operator 3, Telkomsel, Indosat and XL. This tool can send email notifications via the platform thinger.Io to the fire department then Firefighters who receive the email will immediately get ready and rush to the fire location to extinguish the fire and save fire victims.